Construction of unique six-coordinated titanium species with an organic amine ligand in titanosilicate and their unprecedented high efficiency for alkene epoxidation1. Issue 43 (28th May 2015) - Xu, Le; Huang, Da-Ding; Li, Chen-Geng; Ji, Xinyi; Jin, Shaoqing; Feng, Zhaochi; Xia, Fei; Li, Xiaohong; Fan, Fengtao; Li, Can; Wu, Peng
<x xml:space="preserve">Abstract</x> An organic–inorganic titanosilicate with an amine ligand shows high catalytic activity, selectivity and recyclability in alkene epoxidation.